2005
DOI: 10.1242/jcs.02510
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule actin crosslinking factor 1b: a novel plakin that localizes to the Golgi complex

Abstract: MACF1 (microtubule actin crosslinking factor), also called ACF7 (actin crosslinking family 7) is a cytoskeletal linker protein that can associate with both actin filaments and microtubules. We have identified a novel alternatively spliced isoform of MACF1. We named this isoform MACF1b and renamed the original isoform MACF1a. MACF1b is identical to MACF1a, except that it has a region containing plakin (or plectin) repeats in the middle of the molecule. MACF1b is ubiquitously expressed in adult tissues with espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 54 publications
(67 reference statements)
1
87
0
1
Order By: Relevance
“…ACF7/MACF1b is expressed in heart tissue and has been shown to localize to the Golgi complex in two human lung cell lines maintained in culture. 81 In the same study, subcellular fractionation experiments revealed that ACF7/MACF1b was detected principally in the Golgi-enriched fraction but not the endoplasmic reticulum (ER) fraction. Furthermore, ACF7/MACF1b was detected in the cytosol of cells treated with brefeldin A, a Golgi destabilizing agent, resulting in the displacement of the Golgi from the perinuclear region to the cytosol.…”
Section: Involvement Of Plakins In the Trafficking And Localization Omentioning
confidence: 90%
“…ACF7/MACF1b is expressed in heart tissue and has been shown to localize to the Golgi complex in two human lung cell lines maintained in culture. 81 In the same study, subcellular fractionation experiments revealed that ACF7/MACF1b was detected principally in the Golgi-enriched fraction but not the endoplasmic reticulum (ER) fraction. Furthermore, ACF7/MACF1b was detected in the cytosol of cells treated with brefeldin A, a Golgi destabilizing agent, resulting in the displacement of the Golgi from the perinuclear region to the cytosol.…”
Section: Involvement Of Plakins In the Trafficking And Localization Omentioning
confidence: 90%
“…We performed whole-mount immunohistochemistry with anti-MACF1 CU119 antibody (Lin et al 2005) on wild-type and mutant embryos. MACF1 was ubiquitously expressed at E7.5, with the highest levels in the head fold and in the primitive streak of the wild-type embryo (Fig.…”
Section: Generation Of Macf1 −/− Micementioning
confidence: 99%
“…The primary antibodies used include anti-MACF1 (CU119), which recognizes all isoforms of MACF1 (Lin et al 2005), anti-T (brachyury), anti-OTX2 (Santa Cruz Biotechnology), and anti-phospho-Histone H3 (Upstate Biotechnology) antibodies. Phosphorylation of Histone H3 is correlated with chromosome condensation during cell division and used as a marker of cell proliferation.…”
Section: Whole-mount In Situ Immunohistochemistry Hybridization Andmentioning
confidence: 99%
See 1 more Smart Citation
“…We suppose that the interaction between p230 and GSK3 is indirect and that additional TGNassociating protein(s) might be involved in the interaction. One of the most plausible candidates is microtubule-actin crosslinking factor 1 (MACF1) because MACF1 has been shown to interact with GSK3 and p230, localizes to the TGN, and is known to regulate the localization of CLASP2 to the plasma membrane (Chen et al, 2006;Kakinuma et al, 2004;Lin et al, 2005;Drabeck et al, 2006). On the other hand, CLASP2 has been shown to interact with another TGN golgin, GCC185 (Efimov et al, 2007).…”
Section: Gsk3 Localizes To the Tgnmentioning
confidence: 99%